Brown, Michelle P. 2023. Bede and the Theory of Everything. London: Reaktion Books. Pp. 312. ISBN 9781789147889. - Rauer, Christine (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2024)
Book review of Brown, Michelle P. 2023. Bede and the Theory of Everything. London: Reaktion Books. Pp. 312. ISBN 9781789147889.